FREQUENCY OF UNERUPTED MANDIBULAR THIRD MOLAR IN MANDIBULAR ANGLE FRACTURES - Abbasi, Masroor Manshad; Abbas, Irum; Khan, Noreen; Shah, Syed Majid Hussain; Hameed, Hifsa; Shad, Samia; Zulfiqar, Kunwal (Journal of Ayub Medical College Abbottabad, 2012)
Background: Fractures of the mandibular angle are common and comprise 31% of all mandibular fractures. Multiple recent studies report a 2-3 fold increased risk for mandibular angle fractures when un-erupted mandibular third molars are present. The objective of this study was to assess the frequency of un-erupted mandibular third molar in mandibular angle fractures. Methods: This crosssectional study was conducted at the Department of Oral and Maxillofacial Surgery, Ayub Medical College, Abbottabad from April to October 2009. One hundred and two patients were included both from the outdoor and ward on consecutive non-probability sampling base. Data were recorded on a structured Performa and analysed using SPSS-16. Results: A hemi-mandible containing un-erupted mandibular third molar was seen to have a 1.41 times the risk of mandibular angle fracture then a hemi-mandible containing an erupted mandibular third molar. Conclusion: The presence of unerupted mandibular third molar is associated with an increased risk for mandibular angle fracture. Keywords: Maxillofacial trauma, mandibular third molar, mandibular angle fracture